The Role of Strategic Financial Planning in Enhancing Organizational Resilience: A Cross-Industry Perspective - Amir Farouq; Camila Rios (Journal of Management and Informatics, 2025)
This study examines the role of strategic financial planning in strengthening organizational resilience across industries. Using a mixed-methods research design, qualitative data were collected through in-depth interviews with financial managers, while quantitative data were obtained from corporate financial reports across multiple sectors. The integration of these two approaches enables a more comprehensive assessment of how financial strategies influence adaptive capacity, risk preparedness, and long-term organizational stability. The findings reveal that organizations implementing scenario-based planning, sustainability-oriented budgeting, and proactive capital allocation exhibit significantly greater resilience to economic uncertainty and market volatility. Moreover, financial sustainability is identified not only as a key driver but also as a strategic outcome of organizational resilience, reinforcing the interdependence between prudent financial management and adaptive performance. These results offer important managerial implications by demonstrating how strategic financial planning can be operationalized as a resilience-building mechanism across different industrial contexts. From a policy perspective, the study highlights the need for regulatory frameworks that encourage long-term financial sustainability as a foundation for organizational adaptability.